Big Data in Transplantation Practice—the Devil Is in the Detail—Fontan-associated Liver Disease. Issue 1 (January 2021) - Kim, Michelle H.; Nguyen, Ailene; Lo, Mary; Kumar, Subramanyan Ram; Bucuvalas, John; Glynn, Earl F.; Hoffman, Mark A.; Fischer, Ryan; Emamaullee, Juliet
Abstract : Background: As a result of the Fontan procedure, the prognosis of congenital single-ventricle heart disease has improved, with many affected children surviving into adulthood. However, the unanticipated consequences of chronic exposure to Fontan hemodynamics have revealed a new set of secondary noncardiac complications. Fontan-associated liver disease (FALD) is characterized by progressive hepatic fibrosis in nearly all patients post-Fontan, with the potential to develop cirrhosis, hepatocellular carcinoma, and the need for liver transplantation. A lack of data regarding FALD-related prognosis makes consideration of indications for and timing of heart alone versus combined heart-liver transplantation challenging. Methods: A multidisciplinary group within the American Society for Transplantation analyzed several administrative datasets to study the epidemiology of FALD. Results: This approach presented several obstacles, and efforts to characterize FALD were limited by a lack of Fontan- and FALD-specific diagnostic codes and an inability to follow individual patients through multiple health systems. Several ongoing Fontan registries were also reviewed but these do not adequately capture FALD-related variables. Such barriers highlight the need for large-scale data collection in patients post-Fontan to better understand and care for this complex population. Conclusions: This study emphasizes the challenges of studying emerging transplant-related diagnoses in existing datasets and the need for mechanisms to adapt registries to appropriately identify patients with rare or emerging conditions. Abstract : Supplemental Digital Content is available in the text.